New Percutaneous Options for Tricuspid Intervention: How to Identify the Good Clinical Candidate - Laricchia, Alessandra; Khokhar, Arif A.; Giannini, Francesco (Frontiers in Cardiovascular Medicine, 2020)
The tricuspid valve has been neglected for a long time and severe tricuspid regurgitation (TR) was largely undertreated in the past due to a high operative risk. In the last years we observed the development of different less invasive percutaneous options to treat TR. Currently, percutaneous treatments are reserved for high-risk patients presenting with advanced stage disease by which time they are likely to derive a partial benefit at best. There is a limited evidence base, including no randomized trials, to guide the management strategy for severe TR. In the interim we feel that choosing the best device for the most appropriate clinical candidate and with an adequate timing (most probably an “earlier” timing) will be the key combination to improve early and late outcomes of percutaneous treatments.